Recent Advances in Controlling Syntheses and Energy Related Applications of MX2 and MX2/Graphene Heterostructures. Issue 17 (18th April 2016) - Shi, Jianping; Ji, Qingqing; Liu, Zhongfan; Zhang, Yanfeng
Abstract : Recently, two‐dimensional (2D) layered materials have attracted significant attention owing to their novel physical properties and versatile applications in electronics, optoelectronics, and renewable energy storage/conversions. Monolayer transition metal dichalcogenides, for example MX2 (M = Mo, W; X = S, Se, etc.) have become the flagship materials after graphene (Gr), because of their unique properties (e.g., direct bandgaps, strong light‐matter interactions, and high‐efficiency electrocatalytic and photocatalytic activities, etc.). Particularly, vertically stacked MX2 /graphene (MX2 /Gr) heterostructures have also ignited intensive interest, where many unusual physical issues have been detected, and novel devices with unprecedented performances have been constructed. Recent research achievements towards the controllable syntheses of monolayer MX2 and MX2 /Gr heterostructures, as well as their multiple applications in electronics, optoelectronics and energy related fields are highlighted. The first part of this review focuses on the chemical vapor deposition syntheses of high‐quality monolayer MX2 and MX2 /Gr heterostructures on insulating and conducting substrates. The second part introduces the applications of MX2 and MX2 /Gr heterostructures in above‐mentioned application aspects. Finally, remaining challenges for the controllable syntheses and the large‐scale applications of MX2 and MX2 /Gr heterostructures are discussed, and the future research directions in the related fields are also proposed. Abstract : Recent research achievements towards the controllable syntheses of monolayer MX2 and MX2 /Gr heterostructures, as well as their multiple applications in electronics, optoelectronics and energy related fields, are summarized. The remaining challenges for the controllable syntheses and the large‐scale applications of MX2 and MX2 /Gr heterostructures are discussed, and the future research directions in the related fields are proposed.